2016
DOI: 10.1007/s40265-016-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

Rotigotine Transdermal Patch: A Review in Restless Legs Syndrome

Abstract: Rotigotine transdermal patch (Leganto(®), Neupro(®)) is indicated for the treatment of restless legs syndrome (RLS); this article reviews the pharmacological properties of rotigotine transdermal patch and its clinical efficacy and tolerability in patients with RLS. The transdermal patch allows for a continuous, stable release of rotigotine (avoiding first-pass metabolism), which in turn leads to continuous receptor stimulation, believed to closely mimic physiological striatal dopamine receptor function. In sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, some evidence suggests that dysregulation of the dopaminergic system might be involved in the genesis of this disease. In this regard, it has been demonstrated that the use of a dopaminergic agonist, such as rotigotine, induces positive improvements in RLS patients [80][81][82]. Importantly, the study of the neurobiological origins of RLS in aged population is required.…”
Section: Aged Subjects and Restless Legs Syndromementioning
confidence: 99%
“…However, some evidence suggests that dysregulation of the dopaminergic system might be involved in the genesis of this disease. In this regard, it has been demonstrated that the use of a dopaminergic agonist, such as rotigotine, induces positive improvements in RLS patients [80][81][82]. Importantly, the study of the neurobiological origins of RLS in aged population is required.…”
Section: Aged Subjects and Restless Legs Syndromementioning
confidence: 99%